Counter stories: The voices of Indigenous peoples undertaking educative roles in flexi schools - Shay, Marnee; Sarra, Grace; Lampert, Jo (The Australian Journal of Indigenous Education, 2022)
This paper reports on findings from the first author’s doctoral research examining the experiences of Aboriginal and Torres Strait Islander staff in Australian flexi schools. ‘Collaborative yarning methodology’ story boarding was used to hear (and theme) the collective experiences of Indigenous teaching and non-teaching staff in these alternative school settings where both they and Indigenous students make up larger numbers of staff than mainstream schools. Informed by Indigenist and critical race theory, 19 Indigenous staff members contributed to knowledge around three themes: Us Mob; Race and racism, and School Practice which incorporated discussions both of curriculum and of issues related to funding. Many Indigenous staff were working in flexi schools through choice and a sense of commitment to working with Indigenous youth. However other issues, such as experiences of racism, were still present despite the ‘social justice’ nature of flexi schools.